THE SALTOPTERAN FAUNA OF PORTUGAL: NEW RECORDS AND BIOGEOGRAPHICAL ASPECTS (ORTHOPTEROIDEA) - Schmidt, Gerhard H.; Martinho, Ana Paula; Paiva, Maria Rosa (Fragmenta entomologica, 2009)
The saltopteran fauna of Portugal was studied between 1992-2000. Sampling took place during field tlips, lasting yearly 5 to 14 days. Several southern, central and northern regions were visited at different times of the year. In total, 76 species (31 of Ensifera and 45 of Caelifera) were recorded, from which a C/E quotient of 1.45 was calculated. For some of the species caught, the song of the male was presented as additional taxonomic character. First records were made for nine species: Tylopsis lilifolia, Conocephalus conocephalus, Platycleis falx laticauda, two Ctenodecticus spp., Mogoplistes brunneus, Tetrix subulata, Paracimena t. bisignata. Uromenus anapaulae was found as new species and described. Using literature data, the species of Saltatoria previously mentioned for Portugal were listed, and some notes added for insufficiently known species. The biogeography of the saltatoria fauna of Portugal is discussed in relation to its origin with the result that 19 (25%) specis are endemic for the Iberian Peninsula.